2011
DOI: 10.1016/j.jadohealth.2010.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Keeping Adolescent Orphans in School to Prevent Human Immunodeficiency Virus Infection: Evidence From a Randomized Controlled Trial in Kenya

Abstract: Purpose-We report findings from a pilot study in western Kenya, using an experimental design to test whether comprehensive support to keep adolescent orphans in school can reduce HIV risk factors.Methods-Adolescent orphans age 12-14 years (N=105) in Nyanza Province were randomized to condition, after stratifying by household, gender, and baseline survey report of sexual behavior. The intervention comprised school fees, uniforms, and a "community visitor" who monitored school attendance and helped to resolve pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 6 publications
1
67
0
1
Order By: Relevance
“…The findings extend those of a published report of reduced school dropout after two years of comprehensive school support (Hallfors et al, 2011) and are congruent with other findings of schooling subsidies helping SSA adolescents stay in school at one- and two-year follow-up (Baird et al, 2011; Cho et al, 2011). The comprehensive intervention is associated with reduced frequency of both delayed school progression and permanent dropout 2, 3, and 5 years after study onset.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings extend those of a published report of reduced school dropout after two years of comprehensive school support (Hallfors et al, 2011) and are congruent with other findings of schooling subsidies helping SSA adolescents stay in school at one- and two-year follow-up (Baird et al, 2011; Cho et al, 2011). The comprehensive intervention is associated with reduced frequency of both delayed school progression and permanent dropout 2, 3, and 5 years after study onset.…”
Section: Discussionsupporting
confidence: 89%
“…Evans et al (2009) found that uniform provision improved average test score one year after program inception, but not beyond. Cho et al (2011) found that orphan school support reduced drop out after one year. None of these researchers examined normal progression (advancing in grade each year) and only two (Baird et al, 2011; Evans et al, 2009) examined performance (e.g., test scores).…”
Section: Schooling Support As Public Health Strategymentioning
confidence: 99%
“…We conducted the baseline survey using ACASI on personal digital assistant (PDA) devices. The self-administered questionnaire was originally developed from several validated instruments and has been used in a previous pilot study in Kenya24 as well as a similar Zimbabwean study 25. We added several items from the Kenya Demographic and Health Survey (KDHS) 22.…”
Section: Methodsmentioning
confidence: 99%
“…For example, a randomized controlled trial conducted in Kenya implemented an intervention for comprehensive educational support (i.e., school fees, uniforms, community visitor to monitor attendance, etc.) among orphans, and monitored their school attendance and health behaviors over time (65). The researchers found that providing comprehensive educational support not only lowered school absenteeism and dropout but it also had promise to delay sexual initiation and other risk factors associated with HIV.…”
Section: Schoolsmentioning
confidence: 99%